2018
DOI: 10.1016/j.addbeh.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with alcohol consumption among medical cannabis patients with chronic pain

Abstract: High-risk drinking appears common among medical cannabis patients. Future research should examine whether such use is concurrent or consecutive, and the relationship of such co-use patterns to consequences. Nevertheless, individuals treating patients reporting medical cannabis use for pain should consider alcohol consumption, with data needed regarding the efficacy of brief alcohol interventions among medical cannabis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
13
2
Order By: Relevance
“…Few members of our sample reported driving after consuming 4 or more drinks in the same period as they reported DUIC; however, we did not collect data on simultaneous co-ingestion of alcohol and cannabis, which is a direction for future research. A prior examination from these data found that participants who could be classified as "high risk drinkers" had lower pain severity and lower odds of receiving disability benefits compared to non-drinkers and low-risk drinkers, but these groups did not differ in their cannabis consumption (Davis et al, 2018). In current analyses, higher pain was associated with decreased risk for DUIC (within 2 hours and "a little high"), and may be an indicator of how likely these patients are to drive, particularly given that pain conditions could inhibit driving.…”
Section: Discussionmentioning
confidence: 96%
“…Few members of our sample reported driving after consuming 4 or more drinks in the same period as they reported DUIC; however, we did not collect data on simultaneous co-ingestion of alcohol and cannabis, which is a direction for future research. A prior examination from these data found that participants who could be classified as "high risk drinkers" had lower pain severity and lower odds of receiving disability benefits compared to non-drinkers and low-risk drinkers, but these groups did not differ in their cannabis consumption (Davis et al, 2018). In current analyses, higher pain was associated with decreased risk for DUIC (within 2 hours and "a little high"), and may be an indicator of how likely these patients are to drive, particularly given that pain conditions could inhibit driving.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, these results contradict the findings of a Danish cohort study conducted by Ekholm et al (2009) , which concludes that patients with CP are not more likely to consume alcohol (OR = 1.05, 95% CI 0.89-1.24) than people with NCP, but there is risk of higher consumption when people consume opioids (OR = 2.19, 95% CI 1.49-3.23) ( Ekholm, Grønbaek, Peuckmann, Sjøgren, 2009 ). In this line, another study by Davis et al (2018) , found that that high-risk drinkers were also less likely to report a higher severity due to pain (OR = 0.63, 95% CI 0.52-0.77) ( Davis, Walton, Bohnert, Bourque & Ilgen, 2018 ). On the other hand, with respect disability, according to Brennan et al (2005) , 34.2% of men and 28.8% of women who declared that CP interfered with their daily activities, were considered as people with drinking problems ( Brennan, Schutte, Moos, 2005 ).…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, with respect disability, according to Brennan et al (2005) , 34.2% of men and 28.8% of women who declared that CP interfered with their daily activities, were considered as people with drinking problems ( Brennan, Schutte, Moos, 2005 ). On the contrary, according to Davis et al (2018) , high-risk drinkers were less likely to suffer from a disability (OR = 0.41, 95% CI 0.25-0.69) compared with the group without CP ( Davis, Walton, Bohnert, Bourque & Ilgen, 2018 ). However, in our study, no relationship has been found between DCP and this variable.…”
Section: Discussionmentioning
confidence: 98%
“…In an animal model of alcohol preferring rats, stimulation of the CB1 receptor promoted alcohol intake, supporting the hypothesis that the cannabinoid system has modulatory effects on neural circuitry involved in alcohol drinking behaviour (Colombo et al., ). In a recent study, in the United States, a quarter of chronic pain patients using medical cannabis were identified as high‐risk alcohol drinkers (Davis et al., ). Furthermore, the National Academies Committee has concluded that there is moderate evidence for the development of substance dependence and/or abuse disorder in the setting of cannabis use, highlighting the need for vigilance in this regard by the treating physician (National Academies of Sciences E, and Medicine, ).…”
Section: Evidence For Riskmentioning
confidence: 99%